The Effect of Providing Sugarcane Bagasse Biochar and Moringa Leaf Local Microorganism (LMO) on the Growth of Sugarcane Seedlings (Saccharum officinarum Linn) - Kasim, Nurlina; Musa, Yunus; Putri, Nurul Atifah (International Journal of Agriculture System, 2025)
This research aims to study the effect of sugarcane bagasse biochar and Moringa leaf LMO's local microorganisms on sugarcane seedlings' growth. This research was carried out at the experimental garden of the Faculty of Agriculture, Hasanuddin University, Makassar, South Sulawesi, in June - October 2023. This research is arranged in the form of an experiment using a Split Plot Design (SPD), with the main plot being the LMO of Moringa leaves, which consists of 3 levels, namely 0 mL/L water, 200mL/L water, and 400 mL/L water. The subplot is sugarcane bagasse Biochar dosages, which consist of 4 levels, namely 0 g, 50 g, 100 g, and 150 g per plant. Each treatment combination consisted of 3 plant units and was repeated three times, so that there were 108 experimental units. The study results showed no interaction between the LMO concentration of Moringa leaves and the dose of bagasse biochar on all observed parameters. Moringa leaf LMO 200 mL/L water had the best effect on the highest number of tillers. 100 g sugarcane bagasse biochar gave the best impact on the highest chlorophyll levels, the highest chlorophyll b content LMO, and the highest total chlorophyll content, while 150 g bagasse biochar gave the best effect on the highest increase in stem diameter and the highest root fresh weight.